2003
DOI: 10.1046/j.1471-4159.2003.01863.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c, released from cerebellar granule cells undergoing apoptosis or excytotoxic death, can generate protonmotive force and drive ATP synthesis in isolated mitochondria

Abstract: In rat cerebellar granule cells, cytochrome c release takes place during glutamate toxicity and apoptosis due to deprivation of depolarising levels of potassium. We show that, as in necrosis, the released cytochrome c present in the cytosolic fraction obtained from cerebellar granule cells undergoing apoptosis can operate as a reactive oxygen species (ROS) scavenger and as a respiratory substrate. The capability of the cytosolic fraction containing cytochrome c, obtained from cerebellar granule cells undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 75 publications
4
34
0
Order By: Relevance
“…The pellet was resuspended in somatic cell ATP-releasing reagent (Sigma). ATP was determined in the pellet and supernatant as described in Atlante et al (19) with some modifications. The composition of the assay buffer used was 10 mM phosphate buffer (pH 8), 2.5 mM glucose, hexokinase-glucose-6-phosphate dehydrogenase (0.5 specific units) and 0.2 mM NADP.…”
Section: Methodsmentioning
confidence: 99%
“…The pellet was resuspended in somatic cell ATP-releasing reagent (Sigma). ATP was determined in the pellet and supernatant as described in Atlante et al (19) with some modifications. The composition of the assay buffer used was 10 mM phosphate buffer (pH 8), 2.5 mM glucose, hexokinase-glucose-6-phosphate dehydrogenase (0.5 specific units) and 0.2 mM NADP.…”
Section: Methodsmentioning
confidence: 99%
“…36 In addition, the pro-apoptotic shifting to a low potassium medium induced a marked failure of mitochondrial oxidative phosphorylation, accompanied by a dramatic intracellular ATP drop and by an increased production of reactive oxidative species. [37][38][39] A functional impairment of proteasomes, causing a progressive accumulation of ubiquitinated-unfolded proteins in the cytoplasm, 40 and an early perturbation of autophagiclysosomal structures were also revealed in apoptotic neurons. 41 Interestingly, co-culture experiments showed that an Ab antibody partially inhibited the 'transfer' of apoptotic process to healthy, but separated neighboring neurons.…”
Section: Amyloidogenesis and Apoptosismentioning
confidence: 99%
“…On the other hand, among a variety of events occurring during PCD, the release of cytochrome c (cyt c) has been shown both in mammalian and plant mitochondria. In the former case, it was shown that the released cyt c (1) can work as a ROS scavenger and as an electron donor to cytochrome oxidase, thus driving ATP synthesis, which is necessary for apoptosis to occur (Atlante et al, 2003a(Atlante et al, , 2003b and (2) binds to apoptotic protease-activating factor (Apaf-1) protein and, in the presence of ATP/dATP, activates caspase-9, thus triggering activation of a caspase cascade that leads to the morphological changes typical of apoptosis (Li et al, 1997;Zou et al, 1999). In plant cells, cyt c release was already shown in a variety of cases, including menadione-induced death in tobacco protoplasts (Sun et al, 1999), D-Mannose-induced Cyt c release from mitochondria was investigated by immunoblot analysis using a monoclonal antibody against cyt c. Both cytosolic and mitochondrial fractions, obtained from TBY-2 cells subjected to HS (cells in these conditions will be referred to as HS cells), were examined.…”
mentioning
confidence: 99%